The effect of a rehabilitation program on restoring range of motion and strength in wrist joint injuries among boxers - Sakban, Asst.L.Ahmed Abdul Mahdi; Sadiq, L.Dr.Ahmed Ali; Reda, Asst.L.Ali Razzaq (Sulaimani Journal for Humanities, 2025)
The current research aims to develop a rehabilitation program for injured boxers with wrist joint injuries and to determine: Does this rehabilitation program play a role in rehabilitating boxers with wrist injuries? And does it have an effect on restoring range of motion and strength in boxers with wrist joint injuries? To achieve this objective, the researcher employed an experimental approach using a single-group pre-test/post-test design. The researcher defined the research population as five boxers with wrist joint injuries from clubs in Al-Muthanna Governorate. These boxers were selected by distributing questionnaires to boxing clubs in the governorate, as well as to government and private physical therapy centers and specialized clinics. The researcher then conducted a clinical examination to determine the degree of injury and subsequently administered pre-tests to assess the research variables: range of motion (extension, flexion, adduction, and abduction) and strength. The researcher then began implementing rehabilitation exercises for four weeks, with three training sessions per week. Following this, the researcher administered post-tests. After obtaining the results, the researcher used the SPSS statistical software. The results showed that the rehabilitation exercises developed by the researcher had a positive impact on the rehabilitation of injured boxers with wrist joint injuries. This was demonstrated by comparing the pre-test and post-test results across the research variables. The researcher's rehabilitation program had a positive effect on the rehabilitation of injured boxers with wrist joint injuries. One of the most important conclusions reached by the researcher is that the rehabilitation program effectively restored the range of motion in boxers with wrist joint injuries. Furthermore, the rehabilitation program effectively restored strength in boxers with wrist joint injuries. The rehabilitation program also had a very strong effect on restoring both range of motion and strength in boxers with wrist joint injuries.
Keywords: Rehabilitation program; restoring range of motion and strength; wrist joint; boxers